Differential expression of key regulators of Toll‐like receptors in ulcerative colitis and Crohn's disease: a role for Tollip and peroxisome proliferator‐activated receptor gamma?. (26th November 2015) - Fernandes, P.; MacSharry, J.; Darby, T.; Fanning, A.; Shanahan, F.; Houston, A.; Brint, E.
Summary: The innate immune system is currently seen as the probable initiator of events which culminate in the development of inflammatory bowel disease (IBD) with Toll‐like receptors (TLRs) known to be involved in this disease process. Many regulators of TLRs have been described, and dysregulation of these may also be important in the pathogenesis of IBD. The aim of this study was to perform a co‐ordinated analysis of the expression levels of both key intestinal TLRs and their inhibitory proteins in the same IBD cohorts, both ulcerative colitis (UC) and Crohn's disease (CD), in order to evaluate the potential roles of these proteins in the pathogenesis of IBD. Of the six TLRs (TLRs 1, 2, 4, 5, 6 and 9) examined, only TLR‐4 was increased significantly in IBD, specifically in active UC. In contrast, differential alterations in expression of TLR inhibitory proteins were observed. A20 and suppressor of cytokine signalling 1 (SOCS1) were increased only in active UC while interleukin‐1 receptor‐associated kinase 1 (IRAK‐m) and B cell lymphoma 3 protein (Bcl‐3) were increased in both active UC and CD. In contrast, expression of both peroxisome proliferator‐activated receptor gamma (PPARγ) and Toll interacting protein (Tollip) was decreased in both active and inactive UC and CD and at both mRNA and protein levels. In addition, expression of both PPARγ and A20 expression was increased by stimulation of a colonic epithelial cell line Caco‐2 with both TLR ligands and commensal bacterial strains. These data suggest that IBD may be associated with distinctive changes in TLR‐4 and TLR inhibitory proteins, implying that alterations in these may contribute to the pathogenesis of IBD.